Schlitztrommel aus Papua Neuguinea im Ile-Ona Museum of Art and Archival Materials in Iragbiji (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2014)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Artists; Interior decoration; Slit drums; Musical instruments; Museums; Archives; Photographs; Iragbiji; Nigeria; National Archives; Papua New Guinea; New Guinea; Slit Drum (Instrument); Art Collector; Art Collecting